GCxGC/TOF MS technique-A new tool in identification of insect pheromones: Analysis of the persimmon bark borer sex pheromone gland - Kalinová, Blanka; Jiros, Pavel; Zd'árek, Jan; Wen, Xiujun; Hoskovec, Michal (Talanta, 2006)
Conventional gas chromatography with electroantennographic detection (GC-EAD) and two-dimensional (GCxGC) gas chromatography using a time-of-flight mass spectrometric detector (TOFMS), were combined to analyse the female sex pheromone gland extract of the persimmon bark borer, Euzophera batangensis. GC-EAD analysis produced two EAD responses in GC areas where no compounds were detected by FID detection. GCxGC/TOFMS analysis of this area indicated the presence of several chemicals, including (Z9,E12)-tetradeca-9,12-dien-1-ol and (Z9)-tetradec-9-en-1-ol, pheromone components of closely related Euzophera species. Spectral characteristics, retention behaviour and the ability to elicit GC-EAD responses imply that both identified unsaturated alcohols are candidates for E. batangensis sex pheromone components. GCxGC/TOFMS facilitated the analysis of complex matrices on a subnanogram level and was shown to have great potential as a powerful tool in the analysis of insect pheromones.